Antecedent of Continuance Intention on Ride Hailing Application Users in Jabodetabek - Dinda, Prameswari; Risqiani, Renny (Universitas Trisakti, 2025)
This study aims to identify factors influencing continuance intention in ride-hailing apps, examining how perceived usefulness, ease of use, hedonic, and utilitarian values affect trust in platforms and drivers. Non-probability sampling with purposive techniques was employed, involving 200 respondents. Data were analyzed using Structural Equation Modeling (SEM). This study found the antecedents of continuance intention are perceived usefulness, hedonic value, utilitarian value, trust in platform, and trust in driver. It was determined that utilitarian value has the strongest influence on enhancing trust in the platform. Additionally, both trust in the platform and trust in the driver are important considerations for increasing continuance intention. This study may not fully capture all factors influencing platform trust due to the rapidly changing ride-hailing industry, technological advancements, evolving regulations, and intense competition. Additionally, the absence of moderating variables and the diverse demographics of respondents might mean that some values and perceptions are not fully represented. Future research should address these aspects for a more comprehensive analysis. To enhance platform trust, managers can add features like Go Plan, Go Next, Vehicle Filters, and My Reward. To build driver trust, they can improve Vehicle Priority and Subscription Package features. For increasing continuance intention, managers can enhance live tracking, add Check My Ride, and introduce My Guarantee for travel discount vouchers if drivers are late or fail to perform properly. The novelty of this research is its integration of TAM and perceived value to explore trust in platform in ride-hailing apps and its effect on continuance intention.